Інформаційна безпека віддаленої роботи - Щербак, В. О.; Колобилін, І. О. (ХНУРЕ, 2024)
Many companies have started to actively use remote working mode in the last few years. Employees of literally all office ranks are working remotely now, so personal computers are usually used for work, at least as a tool to connect to a remote desktop on a company PC, and most often the personal PC completely replaces the work PC. In this connection, certain questions regarding information security arise.
Keywords: безпека віддаленої роботи; інформаційна безпека віддаленої роботи